An Account on Translators’ and/or Terminologists’ Training at the Universities of Yarmouk and Jordan - Abulhaija, Lutfi (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1992)
AbstractThis article is an account on translators' and/or terminologists' training at both Yarmouk University and the University of Jordan. This account is an attempt to give an idea about training programmes, syllabi, registration prerequisites, teaching methods, degrees and other relevant information. Information was derived through personal contacts with the programmes concerned.